Acute conditions in dermatology: toxic reactions and their treatment - Luiza R. Sakaniya; Kristina T. Plieva; Elena V. Denisova; Irina M. Korsunskaya (ZAO "Consilium Medicum", 2021)
Acute severe conditions caused by the use of various drugs are of particular difficulty in dermatological practice. Toxicodermic reactions include DRESS syndrome, StevensJohnson syndrome, toxic epidermal necrolysis, acute generalized exanthematous pustulosis and erythroderma of various origins. These disorders are characterized not only by skin lesions, but also toxic reactions in internal organs, which if untreated properly can be life-threatening. The first choice drugs for such reactions are systemic glucocorticosteroids, in particular betamethasone derivatives. Our own experience and numerous studies confirm the effectiveness of such drugs. However, it should be remembered that uncontrolled or prolonged use of systemic glucocorticosteroids can aggravate the patient's condition and lead to unwanted adverse reactions.